An SDN-based Energy-Aware Routing Model for Intra-Domain Networks - Celenlioglu, M. Rasih; Goger, S. Burak; Mantar, H. Ali (IEEE, 2014)
Energy has become an important issue in many areas due to increasing energy costs and environmental issues. The Internet is one of the major energy consuming areas. In this paper(1), we proposed an energy-aware routing and resource management model for large-scale networks by adapting an SDN ( Software Defined Networking) based approach. Controller uses pre-established multi-paths ( PMPs) and perform routing, admission control based on these paths. PMPs are turned on or off based on traffic conditions to save energy. The experimental results verify the achievements of the proposed model under various traffic conditions.
22nd International Conference on Software, Telecommunications and Computer Networks (SoftCOM) -- SEP 17-19, 2014 -- Split, CROATIA
Keywords: Software Defined Networking; QoS routing; MPLS; energy efficiency; pre-established path